2007
DOI: 10.1111/j.1462-2920.2007.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the human gastrointestinal tract microbiota revisited

Abstract: SummarySince the early days of microbiology, more than a century ago, representatives of over 400 different microbial species have been isolated and fully characterized from human gastrointestinal samples. However, during the past decade molecular ecological studies based on ribosomal RNA (rRNA) sequences have revealed that cultivation has been able only to access a small fraction of the microbial diversity within the gastrointestinal tract. The increasing number of deposited rRNA sequences calls for the setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
340
1
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(372 citation statements)
references
References 93 publications
17
340
1
8
Order By: Relevance
“…Prior to this investigation, the eukaryotic members of the human gut microbial community have been primarily assessed using cultivation-based methods, and this has led to the belief that they are not widely distributed or abundant in the human microbiota (Rajilic-Stojanovic et al, 2007). This statement is indeed true for the cultivable fraction of the community, but through the application of cultivation-independent techniques, such as DNA extraction and PCR, this study provides evidence that stable eukaryotic communities are widespread in the healthy human gut.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this investigation, the eukaryotic members of the human gut microbial community have been primarily assessed using cultivation-based methods, and this has led to the belief that they are not widely distributed or abundant in the human microbiota (Rajilic-Stojanovic et al, 2007). This statement is indeed true for the cultivable fraction of the community, but through the application of cultivation-independent techniques, such as DNA extraction and PCR, this study provides evidence that stable eukaryotic communities are widespread in the healthy human gut.…”
Section: Discussionmentioning
confidence: 99%
“…Each individual harbours at least 160 such species (11,12) . Under normal circumstances, predominant intestinal microbiota of an adult individual is fairly stable.…”
Section: Human Gut Microbiotamentioning
confidence: 99%
“…The GI tract is colonized with approximately 1000 microbial species, commonly called the microbiota, and may harbor more than nine million unique genes (Zoetendal et al, 2008;Yang et al, 2009). Culture-independent approaches such as ribosomal RNA (rRNA) targeting technologies have revealed that the microbiota is stable in time in healthy adults, and host-and location specific (Rajilić-Stojanović et al, 2007;Zoetendal et al, 2008). Random metagenomic analysis of fecal microbiota suggested that it complements human physiology with a range of essential functions that were canonically encountered in different adults, and that a potential link between microbiota-derived gene pool and health and disease exists (Gill et al, 2006;Kurokawa et al, 2007;Turnbaugh et al, 2009;Qin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%